2011
DOI: 10.1038/leu.2011.326
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of TET2 mutations in acute myeloid leukemia

Abstract: We investigated ten --eleven translocation 2 (TET2) mutations in acute myeloid leukemia (AML), their correlation with other gene mutations and prognostic value. By deep-sequencing, 131 somatic TET2 mutations were identified in 87/318 (27.4%) patients. Of 87 mutated cases, 44 (50.6%) carried two mutations. TET2 mutations were concomitantly observed with mutations in NPM1, FLT3-ITD, FLT3-TKD, JAK2, RUNX1, CEBPA, CBL and KRAS. However, TET2 mutations rarely concomitantly occurred with IDH1mut or IDH2mut (2/251 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
170
4
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(183 citation statements)
references
References 46 publications
7
170
4
2
Order By: Relevance
“…A high frequency of TET2 mutations was also suggested by a small targeted sequencing study (n=5) in which all cases showed changes to this gene 12543/60449 reads). The TET2 insertion has not previously been reported in BPDCN ( Figure 1E and Table 1) but has been found in myeloid diseases (MDS, AML and CMML) 10,11 . RHOA G17V has been found in the T-cell lymphoproliferative diseases, ATLL 12 and AITL 13 and also in 20% (3/15) cases of NK/T cell lymphoma 14 but has also not previously been reported in BPDCN.…”
mentioning
confidence: 87%
“…A high frequency of TET2 mutations was also suggested by a small targeted sequencing study (n=5) in which all cases showed changes to this gene 12543/60449 reads). The TET2 insertion has not previously been reported in BPDCN ( Figure 1E and Table 1) but has been found in myeloid diseases (MDS, AML and CMML) 10,11 . RHOA G17V has been found in the T-cell lymphoproliferative diseases, ATLL 12 and AITL 13 and also in 20% (3/15) cases of NK/T cell lymphoma 14 but has also not previously been reported in BPDCN.…”
mentioning
confidence: 87%
“…TET2 mutations in adult AML commonly co-occur with other somatic mutations including NPM1, RARα, KIT, FLT3, RAS, MLL and C/EBPα [92][93][94][95][96]. ASXL1 mutations occur in adult AML (5-30%) more often in patients over 60 years (16%) than in patients 60 years and younger (3.2%).…”
Section: Clonal Haematopoiesis and Pre-leukaemiamentioning
confidence: 99%
“…TET2 mutations have been identified in approximately 30% of AML cases by deep sequencing [109], usually in combination with other molecular abnormalities, except for IDH1/IDH2 mutations with which they have been shown to be mutually exclusive [110]. It has been reported to occur in >10% of younger AML patients [110].…”
Section: Ten-eleven Translocation 2 (Tet2)mentioning
confidence: 99%
“…It has been reported to occur in >10% of younger AML patients [110]. When present in NPM1 mutated, FLT3-ITD wild-type disease (defined as a favorable risk group, according to European Leukemia Net classification), TET2 mutations confer a poor prognostic impact [26,109].…”
Section: Ten-eleven Translocation 2 (Tet2)mentioning
confidence: 99%